Development of guided inquiry-oriented e-worksheets to improve students' science process skills in acid-base material - Dini Catur Anisah; Harun Nasrudin (Jurnal Pijar Mipa, 2023)
This study aims to describe the feasibility of guided inquiry-oriented E-worksheets to improve students' science process skills on acid-base material. The research method is Research and Development (R&D), using the 4D development model, which is limited to the development stage and limited trials on 38 eleventh grades at Al-Islam Krian senior high school. The results showed the feasibility of E-worksheets as follows : (1) The validity of E-worksheets based on the criteria of content, presentation, language, and graphics, obtained the mode in E-worksheets 1 and E-worksheets 2, respectively: content criteria 5 and 5; presentation criteria 4.5 and 4.5; language criteria 4 and 4; graphic criteria 5 and 5 with valid and very valid categories, so that the developed E-worksheets are feasible based on the validity criteria. (2) The practicality of the E-worksheets is reviewed from the responses and activities of students. Learner responses based on content, presentation, language, and graphic criteria obtained a percentage of 96.42%; 96.70%; 99.12%; and 100% with a very practical category. Relevant learner activities at meeting 1 and meeting 2 received a percentage of 95.02% and 96.56% in the very practical category. (3) E-worksheets' effectiveness is based on improving science process skills. A normality test showed a significant score on the pretest and posttest of 0.004 and 0.000, respectively, so the significance < 0.05 showed that its data was not distributed normally. Furthermore, pretest and posttest data are analyzed using the Wilcoxon signed rank test, with a significance score of 0.000 < 0.05, showing a significant difference in pretest and posttest results. Data pretest and posttest then also analyze using N-gain with a score from 0.70 to 1.00 with a high category, so students' science process skills are said to increase. E-worksheets effectively improve science process skills.